Simulation of operating conditions and working fluids for organic Rankine cycles (2020)
Operating conditions for different fluids in Organic Rankine Cycles using low grade energies were compared. The following fluids were used: R152a (1,1-difluroethane), R-290 (propane), R-600a (2-methylpropane or isobutane), R-744 (CO2) y R-1270 (propylene). Simulation with HYSYS v3.2 was used to support the research. Organic Rankine cycle was studied. Also, the following modifications were studied: reheating, regeneration and reheating-regeneration. Regeneration cycle showed the best results, however, thermal efficiencies were lower than 10%. Operating conditions were simulated in order to increase this value. It was determined that the fluid that presented the best behavior was the R-600a refrigerant, using a Rankine with regeneration cycle operating between 3 500 kPa and 150 ºC at the turbine entrance and 700 kPa in the condenser. A thermal efficiency of 15.33 % was obtained and 7.11 kW of electric power can be produced.